A System Dynamics Approach for Sustainability Assessment of Biodiesel Production in Colombia. Baseline Simulation - Espinoza-Perez, A (Elsevier Ltd, 2019)
The issue of sustainability assessment of biodiesel production has increasingly gained importance due to the interest of governments in drawing up sovereignty strategies, to diversify their energy matrix and to determine the impact of biofuels production. In this context, this work proposes a system dynamics model to assess biodiesel production in a specific context. A System Dynamics model was developed and applied to assess the sustainability of the conditions in the baseline scenario of biodiesel production in Colombia. Simulation of current biodiesel production showed that a strong support from government policies is required related to the promotion of an increase of the contents of biodiesel in the biodiesel-diesel blend, as well as of the production capacity. Certain dynamics were observed as a result of the modeling, the increase oil palm cultivation, can be related to a lesser rate of displacement of the population, of poverty and of emissions of pollutants affecting air quality (hydrocarbons, carbon monoxide and particulate matter). Results also predicted that the increase in oil palm cultivation under baseline scenario could boost inequitable distribution of land ownership and increase greenhouse gas emissions (GHGE) in palm oil cultivation, and reduce food security. © 2018 Elsevier Ltd